CRITICAL THINKING IN EDUCATION - Murodbekov Avazbek; Laylo Alimjonova (Journal of new century innovations, 2022)
In this study, critical thinking skills in educational processes and the value of critical thinking for students enrolled in any educational programme were discussed. The cultivation of an analytical and deductive mindset is given a high priority in today's educational philosophies, practises, and models. The purpose of this research is to develop a conceptual framework for the use of critical thinking in educational settings. As a direct result of the fact that the world is continually growing more technically advanced as well as more complicated, the demand for education continues to rise with the birth of each succeeding generation. Over the course of the last few decades, it has come to be generally accepted that the development of one's capacity for critical thinking is an essential component of education in any discipline. The findings of study allow for broad generalisations to be drawn about the importance of having strong critical thinking skills.